CGIAR water systems integration roadmap 2024–2030: science to transform water systems – creating impact from genes to basins - International Water Management Institute; CGIAR System Organization (International Water Management Institute, 2024)
Challenges in food systems, landscapes and water security call for research and innovation to advance transformation in these systems. Water lies at the center of the integrated approaches needed and it is for this reason that CGIAR and the International Water Management Institute (IWMI) together prepared this CGIAR Water Systems Integration Roadmap 2024–2030.